Implikasi Kesetaraan Gender dalam Pendidikan Islam Studi Analisis Paradigma Fatimah Mernissi - Mubarok, Muhammad Fadhlulloh; Misbah, M. (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Title in Indo Gender equality is the view that all people must receive equal treatment and no discrimination which refers to the rights, responsibilities and equal opportunities of women and men. The purpose of this research is to describe and analyze the implications of gender equality in Islamic education in the Analysis Study of Fatimah Mernissi. The type of research used is library research using a descriptive qualitative approach. The results of this study are that education is the key to establishing gender justice in society, skills and knowledge are also tools for studying and conveying new ideas. Education is a strategic tool in making changes, especially Islamic education. Fatima Mernissi views that education is an initial stage in Islamic education. Where parents act as the first teacher at home. Learning materials as well as knowledge of religion, culture and social customs. In this case Fatima explained that between women and men, both of them are educators and students, they all have the same learning opportunities because they have the same responsibilities. This already happened at the time of the Apostle, he did not divide his people just because of religious and worldly issues, such as social and individual matters. Fatima views that the problem of differences between men and women will continue to exist but within reasonable limits and without eliminating aspects of freedom of human rights that are inherent in her, as well as individual and social human rights responsibilities.